Serosurvey and associated risk factors for Neospora caninum infection in Egyptian water buffaloes (Bubalus bubalis) - Ayed Alshammari; Mohamed Marzok; Hattan S. Gattan; Mohamed Salem; Omar A. Al-Jabr; Abdelfattah Selim (Scientific Reports, 2023)
Abstract Neosporosis is a parasitic disease that causes reproductive disorders in animals, making it a barrier to maximum efficiency. The purpose of this study was to determine the seroprevalence of Neospora caninum (N. caninum) antibodies in water buffaloes from four governorates in northern Egypt. A commercial indirect-ELISA test was used to detect antibodies against N. caninum in the serum of 450 water buffaloes. The total seroprevalence of N. caninum in water buffaloes from Egypt was 31.3%, and the highest prevalence was observed in Gharbia governorate. The identified risk factors for N. caninum infections in water buffaloes were sex (OR = 1.96, 95%CI: 1.22−4.17), buffaloes more than 4 years of age ( OR = 5.80, 95%CI: 2.26−14.86), abortion in second trimester (OR = 16.48, 95%%CI: 2.99−34.03), history of abortion (OR = 3.45, 95%CI: 1.58−7.52) and contact with dogs (OR = 2.55, 95%CI: 1.51−4.32). Thus, more studies are needed to determine the role of buffaloes in the epidemiology of neosporosis in Egypt.